Abul Kalam Azad’s Idea Of Religious Pluralism For An Inclusive Indian Nationalism A Civilizational Revisit - Md Yousuf Ali; Osman Bakar (IIUM Press, 2024)
Al-Shajarah ISTAC Journal of Islamic Thought and Civilization, Volume 28 Issue 2, Page (343–365)